GERAKAN PEDULI KEBERSIHAN MANDIRI (KALI BERSAMA) - Indah Laily Hilmi; Salman Salman; Hadi Sudarjat; Gun Gun Gumilar; Munir Alinu Mulki (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2022)
The Gerakan Peduli Kebersihan Mandiri (Kali Bersama) is an initiative carried out by the Pharmacy students of Singaperbangsa University Karawang with the aim of raising awareness among teenagers in Citra Kebun Mas Housing, Karawang about clean and healthy living behaviors, especially handwashing with soap. This research aims to improve teenagers' understanding of Clean and Healthy Living Behavior (PHBS) and proper handwashing techniques. The method used in this research is counseling, which includes education on the importance of PHBS and demonstration of proper handwashing techniques. The questionnaire results conducted after the counseling show that the majority of teenagers are aware of PHBS and apply it in their daily lives, but there is still a gap between knowledge and PHBS practices. Based on these results, it is recommended to adjust the timing of activities, involve faculty leaders, and provide adequate facilities for the handwashing program with soap in future activities.